Media, terrorism, and theory : a reader - Kavoori, Anandam P.; Fraley, Todd, 1972- (Critical media studies., 2006)
Over the past few years, media outlets have spotlighted coverage of terror attacks. Drawing on both popular and academic articles, [this book] analyzes the larger issues surrounding media's studies, architecture, and information science, each contributor brings a distinctive perspective. Answering a growing need to understand media discourse on terrorism, this volume complements readings in upper-level mass communication courses and is a valuable resource for scholars of international media and terrorism.-Back cover.